Towards a Computer Vision System for Monitoring and Stimulation of Rodents - Lima, Renan Araújo de; Silva, José Wanderson Oliveira; Gonçalves, Luiz Marcos Garcia (Anais Estendidos da Conference on Graphics, Patterns and Images (SIBGRAPI); 2022: Anais Estendidos da XXXV Conference on Graphics, Patterns and Images, 2022)
The Behavioral Neurophysiology research area investigates the electrophysiological correlates of behaviors, normally using animals such as rodents as subjects. Examples of studies in the field include the investigation of neural processing dysfunctions and synaptic plasticity in animal models of autism and changes in synaptic plasticity in animal models of epilepsy. This area is in constant need of new equipment to aid research. With this goal, this work aims to develop a system capable of receiving video information in real-time using computer vision algorithms to define the positioning of the animal, plus the processing of ultrasound audio and brain electrophysiology signals. These data are to be represented in a user-friendly way and, from these data, we also aim to generate brain stimuli depending on the type of test being performed.